[Rezension von: Bloch, Alice, 1964-, Living on the margins] - Jacqmin, Arianna (Oñati Socio-Legal Series, 2017)
Book review of Living on the margins. Undocumented migrants in a global city, by Alice Bloch and Sonia McKay. Bristol: Policy Press, 2016. 9781447319368 (Hb) £56.00, 9781447319375 (Pb) £19.99, 9781447319405 (EPUB) £19.99.Reseña de Living on the margins. Undocumented migrants in a global city, por Alice Bloch y Sonia McKay. Bristol: Policy Press, 2016. 9781447319368 (Td) £56.00, 9781447319375 (Tb) £19.99, 9781447319405 (Web) £19.99.